Statistical Relationship Between Interplanetary Magnetic Field Conditions and the Helicity Sign of Flux Transfer Event Flux Ropes. Issue 6 (18th March 2021) - Kieokaew, R.; Lavraud, B.; Fargette, N.; Marchaudon, A.; Génot, V.; Jacquey, C.; Gershman, D.; Giles, B.; Torbert, R.; Burch, J.
Abstract: Flux transfer events (FTEs) are transient phenomena produced by magnetic reconnection at the dayside magnetopause typically under southward interplanetary magnetic field (IMF) conditions. They are usually thought of as magnetic flux ropes with helical structures forming through patchy, unsteady or multiple X‐line reconnection. While the IMF often has a non‐zero B Y component, its impacts on the FTE flux rope helicity remain unknown. We survey Magnetospheric Multiscale (MMS) observations of FTE flux ropes during years 2015–2017 and investigate the solar wind conditions prior to the events. By fitting a force‐free flux rope model, we select 84 events with good fits and obtain the helicity sign (i.e., handedness) of the flux ropes. We find that positive (negative) helicity flux ropes are mainly preceded by positive (negative) B Y component. This finding is compatible with flux ropes formed through a multiple X‐lines mechanism. Plain Language Summary: The Earth's near‐space environment is very dynamic with transient phenomena triggered by interaction between the solar wind and the Earth's magnetopause. The solar wind carries along an interplanetary magnetic field (IMF) whose orientation determines the dynamics of the interaction. When the IMF is southward, magnetic reconnection can be triggered at the Earth's magnetopause on the dayside. A flux transfer event (FTE) is a transient portal that allows the bursty transfer of solar wind into the Earth's magnetosphere. An FTE is envisaged as a twisted magnetic field structure with helical field that looks like a rope. We study the relationship between the IMF orientations and the twist direction of an ensemble of FTEs observed by NASA's Magnetospheric Multiscale mission, by modeling FTEs as magnetic flux ropes. We found that the flux rope twist direction is controlled by the IMF orientation, such that the rope is twisted in the left‐handed or right‐handed sense depending on the east‐west component of the IMF. This result supports the formation of FTEs by a multiple reconnection mechanism. Key Points: The helicity sign of 84 flux transfer events (FTEs) is studied using force‐free flux rope model fitting Right‐handed (left‐handed) FTE flux ropes are mostly preceded by positive (negative) interplanetary magnetic field (IMF) B Y This IMF B Y control of the helicity sign is compatible with a multiple X‐line formation mechanism